Stories of detection and mystery Agatha christie...[Et el.] Retold by E.J.H. Morris and D.J.Mortimer ; Edited by Andy Hopkins, Jocelyn Potter - Christie, Agatha; Hopkins, Andy; Morris, E.J.H; Mortimer, D.J; Potter, Jocelyn (England, UK Pearson longman, 2008)
Penguin Reader are simplified texts wich provide a step-by-step approach to the joys of reading for pleasure
level 5 2300 headwords
Upper-Intermediat
12
Keywords: English as a second language; English language -- Pronunciation; English stories; Literature; Vocabulary; Word skills